Estudo da atividade ansiolítica e imunomoduladora do Gama-terpineno - Monteiro, Talissa Mozzini (2018)
Inflammation is generated in response to noxious stimuli, such as pathogens, and may be associated with an acute pathogenesis or progress to a chronic process. Gamma-terpinene (GT) is a monoterpene that, in previous studies, presented antiinflammatory action in acute inflammatory processes. The present work aimed to elucidate the anti-inflammatory and anxiolytic mechanisms of GT in murine models of acute (Acute Pulmonary Injury - ALI) and chronic inflammation (rhinitis and asthma). For this, BALB/c mice were challenged with lipopolysaccharide (LPS) to induce ALI and were treated one hour post challenge with GT (12.5, 25 and 50 mg/kg) for three days. After 72 h the animals were euthanized for collection of bronchoalveolar lavage fluid (BALF). For murine models of rhinitis and asthma, BALB/c mice were sensitized and challenged with ovalbumin (OVA) and were treated with GT (12.5; 25 and 50 mg/kg) or standard drug (dexamethasone 2 mg/kg) 1 h before each challenge with OVA. After the last challenge, animals were submitted to clinical symptoms analysis of rhinitis and anxiety and immunological tests in the asthma model. In the ALI protocol, animals GT-treated (50 mg/kg) presented, in nasal fluid lavage (NALF), a decrease in the migration of total and differential cells (neutrophils and mononuclear cells), total protein concentration, as well as lung weight, when compared with OVA group. Histopathological studies showed that treatment with GT50 decreased the cellular infiltrate in the alveolar and vascular regions, edema and hemorrhage. In immunological parameters, GT50 treatment presented a decrease in inflammatory cytokines, such as IL-1β, IL-6 and TNF-α, as well as decreases in the expression of the TLR4 receptor, p38 MAPKinase and p65NFkB. In rhinitis protocol, treatment with GT50 showed a decrease in clinical symptoms, such as nasal friction and sneezing, in addition to a decrease in BALF of total and differential cells, mainly eosinophils. Histopathological analyses of the nasal cavity, the treatment with GT50 promoted a decrease in cell infiltrate, mucus secretion and mast cell number. The treatment with GT50 in asthma protocol showed a significantly decrease in anxiety rates compared to OVA animals (sick), effect similar to diazepam (1 mg/kg), presenting an anxiolytic effect. Treatment with GT50 also decreased c-fos expression in brain areas such as the hypothalamic paraventricular nucleus (PVN) and central nucleus of the amygdala (CeA) when compared to the OVA group. In the histological analyzes there was a decrease in cell infiltration and mucus secretion in the lung tissue. In addition, treatment with GT50 decreased immunological parameters such as: IgE-OVAspecific levels; migration of total and differential cells mainly eosinophil in BALF and modulation of the Th2 response by inducing both Th1 profile by secretion of IFN cytokine and regulatory profile, by secretion of cytokine IL-10. Treatment with GT50 was also able to decrease Th2 profile cytokines, such as IL-4 and IL-13, in addition to decreasing the activation of p38 MAPquinase and p65NFkB receptor expression. These data indicate that GT has both anxiolytic and anti-inflammatory properties in acute and chronic processes by inhibition of MAP kinasep38 and the transcription factor NFκB.